Retrospective Analysis of a Modified Irrigation Method for Nasopharyngeal Carcinoma Patients With Post-Radiation Nasopharyngeal Necrosis - Xiao, Yun; Peng, Shiyi; Tang, Yiqiang; Xie, Honghui; Huang, Min; Wang, Jing; Gong, Xiaochang; Li, Jingao (Frontiers in Oncology, 2021)
Purpose: Post-radiation nasopharyngeal necrosis (PRNN) is one of the most serious late effects of nasopharyngeal carcinoma (NPC) after radiotherapy. Standard conservative treatments are not always effective, and this study sought to investigate the feasibility of modified nasopharyngeal irrigation in the treatment of PRNN. Methods: Between September 2011 and September 2018, 113 NPC patients with pathologically or radiologically diagnosed PRNN were analyzed retrospectively. All patients received the traditional conservative treatments of debridement of the necrotic tissues guided by an endoscope and systematic antibiotic therapy partly guided by culture results. The patients were divided into two groups according to the irrigation method used: traditional and modified groups. Modified irrigation used an irrigation device made by our hospital, guided by endoscopy, while the patients in the traditional irrigation group used a nasopharyngeal irrigation pot to wash the nasopharynx by themselves each day. Results: Survival was affected by ICA (internal carotid artery) exposure, necrosis grade, and re-irradiation, but only ICA exposure and re-irradiation were found to be independent prognostic factors. The modified irrigation had a significantly more positive effect on the recovery rates of patients with mild- and moderate-grade PRNN than did traditional irrigation. The 2-year overall survival (OS) of the 113 patients was 68.4%. The modified irrigation was associated with better OS in the mild- and moderate-grade groups, in the one-course radiotherapy group, and in the low-risk group (according to the 2017 system). Conclusions: More intense modified irrigation under the physician's control may be an effective treatment for PRNN, especially mild- and moderate-grade, one-course radiotherapy, or low-risk PRNN.